Alterations in filamin mutations fine tune muscle protein aggregates - Kotala, Kerttu (2024)
Myofibrillar myopathies are genetically inherited, incurable muscle disorders which cause progressive muscle weakness in skeletal muscles. A subtype of myofibrillar myopathy called filaminopathy is caused by aggregation of filamin C and actin in the sarcomeric structures of skeletal muscle fibers. In this Pro Gradu, the aggregation of filamin was investigated in the indirect flight muscles of Drosophila melanogaster by expressing an open conformation mutation separately in one domain pair and two domain pairs. The mutations were located in the mechanosensory region of filamin and they were assumed to open the structure of the domain pairs. I found that single-open mutation resulted in less aggregates than double-open mutation. However, single-open aggregates were larger and less round than double-open aggregates. Also, single-open aggregates located in muscle fiber Z-disc structures whereas double-open aggregates located in between myofibrils. Upon time, single-open aggregates’ volume increased, and shape developed to rounder. These findings suggest that, firstly, an open conformation mutation in one domain pair is enough for aggregate formation. Secondly, differing mutations might affect the localization of forming aggregates during tissue development. And finally, the localization of aggregates restricts the shape development of the aggregates. These detailed findings were partly unexpected and shed light on mechanisms of sarcomeric protein aggregate formation and clearance in muscle.